Pengaruh Kepercayaan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan dengan Pendekatan Deskriptif dan Verifikatif - Udin Syamsudin; Ahmad Fauzan (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2023)
The development of the current digital era, makes it easy for consumers to make buying and selling transactions of goods. This is an indicator for several outlets to start implementing sales with an online system. This system has also begun to be applied to sellers in the fashion industry. Since the Covid-19 pandemic around 2020, the fashion industry has relied heavily on online system sales. This change in behavior has made many fashion companies close their outlets and also switch to using digital technology. Conventional clothing sellers must be able to compete, and be more adaptive to changes in fashion models that change rapidly. This phenomenon is the background for researchers to determine the impact of customer satisfaction and trust on customer loyalty at Victoria Fashion. This research was conducted quantitatively using a descriptive and verification approach. Even though the population size is unknown, a purposive sampling technique was used for sampling. The SPSS Version 20 program was used to analyze data using multiple linear regression techniques. The results of the analysis show that the trust variable has no significant effect on customer loyalty; however, the satisfaction variable has a significant effect on customer loyalty. Based on the research, it is suggested that Victoria Fashion continues to increase customer trust and satisfaction by maintaining the brand of clothing that the customer likes and offering other brands to increase customer satisfaction. And consider setting prices in accordance with the customer's economy